STUDI KOMPARASI KESAKSIAN WANITA DALAM HUKUM PIDANA ISLAM DAN HUKUM PERDATA ISLAM - Abdul Rahim; Kasman Bakry (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This study explains that in the view of Islamic law on women's testimony in Islamic criminal law is that in Jarimah ?ud?d, kisas and takzir there are two conditions that could have occurred. Therefore, the two legal studies have similarities and differences, the location of the similarities can be seen from their position as well as their role as witnesses, namely in terms of their position as one of the evidences in the process of problem solving and in terms of their roles equally contributing to provide true information in accordance with what women see, hear and / or feel / experience it yourself. Whereas the difference in general is that in Islamic criminal law, jumhur ulama are of the opinion that a woman's testimony is rejected, meaning that a minority is accepted, and even then in a very urgent situation, while in Islamic civil law all ulama are of the opinion that a woman's testimony is accepted meaning that there is not a single ulama who reject it and there are even some cases that prioritize women's testimonies over men's testimonies namely issues that are specifically in the area of women.